Planificación estratégica de importaciones y control de la cadena de suministros para empresas con certificación BPADT – buenas prácticas de almacenamiento, distribución y transporte - Coello Guillén, Luis Felipe (2023)
The present study entitled "Strategic planning of imports and control of the supply chain for companies with BPADT certification - Good storage, distribution and transport practices", addresses the problem of how strategic planning affects the control of the supply chain of the main companies with BPADT certification. Which originated from a competitive scenario and with great challenges in the supply processes to the Guayaquil market. The objective was to analyze the incidence of strategic planning in this control process of said supply chain during the period 2018 - 2021. The context of approach is represented by five BPADT certified companies that operate in the city of Guayaquil. The methodology was of a qualitative approach, using three types of qualitative techniques, interviews with company representatives, pest analysis and SWOT. The results showed in general terms the increase in the costs of logistics, transportation and some items in the medical equipment market. The risks found are associated with the logistics and transportation process, unexpected changes in tariff headings, expiration dates and incorrect handling of products, inflexible deadlines, process and storage controls, and inventory maintenance. The contributions through the proposal are oriented to the optimization of the PE of the supply chain of the distributors of medical devices with BPADT certification. These include 3 major strategic actions focused on processes, where the failure is. Improvement of customer service, optimization of logistics processes, increase the profitability of companies, immersed in a strategic management plan, under an assisted forecast methodology, analyzed under the statistical method of forecast.